The Spirit‐led Church: Mission in Action in the Contemporary World. (18th June 2019) - Alva, Reginald
Abstract: We live in a world where technology is radically changing the way we live. The rapid development in the fields of science, especially artificial intelligence, cloning, and stem cell technology, is making our lives more convenient; however, it is also giving rise to a plethora of new ethical issues. Further, weakening of organized religions, moral depravity, and loss of societal values are making society more complex and vulnerable. In such a context, what would be the mission of the church in the contemporary world? How can the church help those who are seeking to know the meaning of their lives? Christians believe that the Holy Spirit is the protagonist in the life of the church. How can the church be truly Spirit led in fulfilling its mission in the world? This article focuses mainly on the mission of the Catholic Church in the contemporary world. The main sources of the study are the documents of the Second Vatican Council, church documents, especially on mission, and views of experts in missiology.